Analisis Tax avoidance dan Earnings management Sebelum dan di Masa Pandemi Covid-19 - Yuli Ardiany; Melli Herfina; Sri Yuli Ayu Putri (Jurnal Ecogen, 2022)
The purpose of this study is to analyze and provide empirical evidence regard-ing Tax avoidance and Earnings management before and during the Covid-19 pan-demic. This type of research is comparative, the data collection method used is library research and online research. The data collection technique in this research is the documentation technique. The population in this study are companies in the trade, services, and investment sectors listed on the IDX in 2017-2020. The sampling method is purposive sampling. The analytical method used is independent sample t-test analysis. From the results of the first Paired Sample T-Test, there is no a significant difference in the tax avoidance and earnings management companies in the trade, services, and investment sectors listed on the IDX in 2017-2020,  variable both before the pandemic and during the Covid-19 pandemic at a significance level of 5% .